PENGARUH MOTIVASI DAN KEBUTUHAN MAHASISWA TERHADAP MINAT MENABUNG DI BANK SYARIAH - Zakia Gigih; Habriyanto; Ahmad Syukron Prasaja (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to analyze and determine the effect of student motivation and needs on interest in saving in Islamic banks. This study uses a sample of 75 from a population of 301. The analysis technique uses instrument testing, classical assumption testing, and hypothesis testing. By using descriptive quantitative research method with research results showing that the independent variables (motivation and needs of students) have a positive and significant influence on the dependent variable (interest in saving). this is evidenced by the partial t test with a value of: Motivation 2.487 > 1993 significant 0.015 < 0.05, Student Needs 4.903 > 1.993 significant 0.000 < 0.05. The value of the coefficient of determination is 0.543 or 54.3% which shows the value of interest in saving is influenced by the motivational variables and student needs, while the remaining 45.7% is influenced by other variables not examined in this study.